2019
DOI: 10.20944/preprints201911.0377.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a 3D-Printable Ultra-High Performance Fiber-Reinforced Concrete for Digital Construction

Abstract: This paper presents the systematic development and performance characterization of a nonproprietary 3D-printable ultra-high-performance fiber-reinforced concrete (UHPFRC) for digital construction. Several fresh and hardened properties of the developed 3D-printable UHPFRC matrix (without fiber) and composite (with 2% volume fraction of steel fibers) were evaluated and compared to that of conventionally mold-cast UHPFRC. Additionally, the effects of testing direction on the compressive and flexural strengths of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It has been established that when the average length of reinforcing fibres exceeds the diameter of the nozzle, they line up along the direction of movement through the nozzle, as depicted in Figure 2, as presented by Zhang et al (2021). Research has shown that aligning the fibres in parallel with the printing direction improves printed samples' bending resistance compared to traditionally cast counterparts (Arunothayan et al, 2020;Ziaee et al, 2022;Zhou et al, 2023). This effect can be explained by the fact that the maximum bridging effect will take place when fibres are oriented perpendicular to the crack.…”
Section: Materials Innovation In 3dpcmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been established that when the average length of reinforcing fibres exceeds the diameter of the nozzle, they line up along the direction of movement through the nozzle, as depicted in Figure 2, as presented by Zhang et al (2021). Research has shown that aligning the fibres in parallel with the printing direction improves printed samples' bending resistance compared to traditionally cast counterparts (Arunothayan et al, 2020;Ziaee et al, 2022;Zhou et al, 2023). This effect can be explained by the fact that the maximum bridging effect will take place when fibres are oriented perpendicular to the crack.…”
Section: Materials Innovation In 3dpcmentioning
confidence: 99%
“…The study examined how the testing direction affected the compressive strength and rupture modulus of 3D-printed ultra-high-performance fibrereinforced concrete. Furthermore, it investigated the relationship between fibre orientation and the mechanical properties of the printed samples (Arunothayan et al, 2020;Arunothayan et al, 2021). Given the increasing need for higher safety standards in civil engineering worldwide, it has become essential to comprehend the dynamic mechanical properties.…”
Section: Fibre Utilization In 3dpcmentioning
confidence: 99%
See 1 more Smart Citation